Preparation of a whey-based probiotic product with Lactobacillus reuteri and Bifidobacterium bifidum - Hernandez-Mendoza, Adrian (Array, 2007)
Lactobacillus reuteri and Bifidobacterium bifidum were inoculated (2.8·108 and 4.7·108 CFU/mL, respectively) into reconstituted whey containing sucrose and pectin in order to prepare a fermented probiotic product. Inoculation levels were: 0.5, 1 or2 % for Lactobacillus reuteri and 0.5 or 1 % for Bifidobacterium bifidum. The treatment with the highest bacterial counts and sensory scores was selected and stored at 4 °C for 30 days. Microbial counts, changes in pH values, titratable acidity and both triangle test and sensory attributes were monitored on the stored product. The beverage fermented for approx. 11 h and prepared with 2 % Lactobacillus reuteri and 0.5 % Bifidobacterium bifidum met the probiotic criterion by maintaining both bacterial populations at counts greater than 106 CFU/mL for the whole storage period. Titratable acidity and pH values as well as sensory properties did not change appreciably during the first 14 days of storage. At the end of the storage period (30 days), slight acidification was detected, although the beverage still retained an acceptable flavour